2023
DOI: 10.1002/fsn3.3460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic mulching on moisture and temperature of soil in greenhouse production of tomato under unheated greenhouse cultivation in the cold zone of China

Abstract: In the cold zone of China, winter is cold and long and has a short duration of sunshine. Unheated earthen‐wall solar greenhouses are used for tomato production in winter in this region. This was an experimental investigation of different organic mulching materials (newspaper, bran, and grass) on the soil temperature, soil moisture, tomato yield, fruit quality, and water use efficiency. Organic mulching variously improved soil temperature, soil moisture, water use efficiency, and tomato yield, which is very imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
2
0
0
Order By: Relevance
“…At the same time, the fluctuation at the 30 cm soil layer in CK was lower than that in MB and DB due to its weak ability to collect rainwater and inhibit evaporation. For the entire growth period, the average soil water content of the 0-30 cm soil layer in MB was 27.4% higher than that in DB and 70.8% higher than that in CK, indicating that MB treatment has a better water-retention effect, which is in agreement with the findings of Zhang et al [25] and Zhao et al [26]. Different organic mulching materials (newspaper, bran, and grass) used in cold regions of China by Zhang et al [25] showed that soil water content in newspaper mulching increased by 14.1% compared with bare land.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At the same time, the fluctuation at the 30 cm soil layer in CK was lower than that in MB and DB due to its weak ability to collect rainwater and inhibit evaporation. For the entire growth period, the average soil water content of the 0-30 cm soil layer in MB was 27.4% higher than that in DB and 70.8% higher than that in CK, indicating that MB treatment has a better water-retention effect, which is in agreement with the findings of Zhang et al [25] and Zhao et al [26]. Different organic mulching materials (newspaper, bran, and grass) used in cold regions of China by Zhang et al [25] showed that soil water content in newspaper mulching increased by 14.1% compared with bare land.…”
Section: Discussionsupporting
confidence: 91%
“…For the entire growth period, the average soil water content of the 0-30 cm soil layer in MB was 27.4% higher than that in DB and 70.8% higher than that in CK, indicating that MB treatment has a better water-retention effect, which is in agreement with the findings of Zhang et al [25] and Zhao et al [26]. Different organic mulching materials (newspaper, bran, and grass) used in cold regions of China by Zhang et al [25] showed that soil water content in newspaper mulching increased by 14.1% compared with bare land. Ridge furrows with plastic film mulching (RP) and flat soil surfaces with plastic film mulching (FP) conducted in the Loess Plateau of China by Zhao et al [26] showed that deep soil moisture was better transferred to topsoil, making the topsoil moisture higher in the FP and RP treatments than the bare land.…”
Section: Discussionsupporting
confidence: 91%